Fan fiction: troubling desire through text - Alcalá Espinosa, Ana (Tropelías: Review of Literary Theory and Comparative Literature, 2023)
This essay explores the possibilites of fanfiction as a disruptive literary genre, which opens a path for the inscription of alternative subjectivities. Fanfiction authors write about their desires at the same time that they explore subjectivities through the text that have been pushed to the margins of society throughout history (such as homosexuality, transgender and female experiences). But. how do they write this, exactly? Thanks to the analysis of two fanfiction texts, we can see how the authors play with the limits of desire, sex, gender and body.